Development of E-Comic-Based Mathematics Teaching Materials on the Topic of Multiplication and Division with Realistic Mathematics Education (RME) Approach - Widyasari, Nurbaiti; Nurcahyani, Anisa (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2021)
The purpose of this study was to develop E-Comic-based mathematics teaching materials on the topic of multiplication and division with the Realistic Mathematics Education (RME) approach. This research is a research and development using the Hannafin and Peck development model. This model consists of three stages, namely needs assessment, design, development and implementation. The subjects in this study were students of class 3A SDN Pinang 2 Tangerang City. The results research obtained included 1) material expert validation got 95,38% with very valid criteria, 2) linguist validation got 87,5% with very valid criteria, 3) media expert validation got 97,5% with very valid criteria. Assessment of student responses 1) small group test got 95,41% with high criteria, 2) large group test got 99% with high criteria. Based on the results of the assessment, the E-Comic-based mathematics teaching materials developed are valid and can be used as additional teaching material for teaching the concept of multiplication and division.Tujuan penelitian ini adalah mengembangkan bahan ajar matematika berbasis E-Comic pada topik perkalian dan pembagian dengan pendekatan Realistic Mathematics Education (RME). Penelitian ini merupakan penelitian pengembangan (Research and Development) dengan menggunakan model pengembangan Hannafin dan Peck. Model ini terdiri atas tiga tahap, yaitu penilaian kebutuhan, desain, pengembangan dan implementasi. Subjek pada penelitian ini adalah peserta didik kelas 3A SDN Pinang 2 Kota Tangerang. Analisis data yang digunakan adalah deskriptif kuantitatif dengan persentase. Hasil penelitian yang didapatkan antara lain 1) validasi ahli materi mendapatkan 95,38% dengan kriteria sangat valid, 2) validasi ahli bahasa mendapatkan 87,5% dengan kriteria sangat valid, 3) validasi ahli media mendapatkan 97,5% dengan kriteria sangat valid. Penilaian respon peserta didik 1) uji kelompok kecil mendapatkan 95,41% dengan kriteria tinggi, 2) uji coba kelompok besar, mendapatkan 99% dengan kriteria tinggi. Berdasarkan hasil penilaian tersebut maka bahan ajar matematika berbasis E-Comic yang dikembangkan valid dan dapat dijadikan sebagai bahan ajar tambahan untuk pengajaran konsep perkalian dan pembagian.